Analisis Peran Evaluasi Pembelajaran dalam Meningkatkan Efektivitas Proses Pembelajaran - Nur Zaskyah; Risma Handayani; Nurnanensi; Nurfadilah; Fajar Maulana; Muhammad Zulfikar (Al-Kindi, 2026)
Learning evaluation is an important component in the educational process, serving to measure the level of achievement of learning objectives, determine student progress, and assess the effectiveness of methods and strategies used by educators. This study aims to analyze the role of learning evaluation in improving the effectiveness of the learning process. The method used is library research by reviewing various literature, scientific journals, books, and relevant sources related to learning evaluation. The results of the study indicate that learning evaluation plays a very important role in providing feedback for teachers and students, identifying the strengths and weaknesses of the learning process, and serving as a basis for decision-making for learning improvement and development. Evaluation carried out in a planned, systematic, and sustainable manner can improve the quality of learning, encourage student learning motivation, and assist teachers in implementing more effective learning strategies. Thus, learning evaluation functions not only as a tool for measuring learning outcomes, but also as a means to improve the quality and effectiveness of the learning process as a whole.